La presencia del notario en las sesiones de directorio y su certificación de las actas societarias - Peró Mayandía, Mariano (Pontificia Universidad Católica del Perú, 2015)
Corporate bodies are essential for the development of companies activities, and their minutes provide a means of evidence and proof of the deliberations and resolutions adopted therein. In certain conlict situations, the presence of a notary public is required in the meetings in order to verify the legality and validity of the resolutions adopted. This is why the General Corporations Law provides for the possibility that the notary public witnesses the general shareholders meeting, but omits it in the case of the board of directors. In this context, the amendment of article 170 of the General Corporations Law expressly incorporates the possibility of counting with the presence of a notary public in the board of directors in order to certify the authenticity of the resolutions and implement immediately the decisions adopted by both corporate bodies.

Los órganos sociales son esenciales para el desarrollo de las actividades de las sociedades y sus actas constituyen un medio de constancia y prueba de las deliberaciones y acuerdos adoptados en ellos. En ciertas situaciones confictivas, se amerita la presencia de un notario en las reuniones para dejar constancia la legalidad y validez de los  acuerdos adoptados. Por ello, la Ley General de Sociedades preveía la posibilidad de que el notario presencie las juntas generales de accionistas, pero lo omitía en el caso del directorio. En este contexto, la modiicación del artículo 170 de la Ley General de Sociedades incorpora de manera expresa la posibilidad de contar con la presencia de un notario en el directorio para certiicar la autenticidad de los acuerdos y poder ejecutar de inmediato las decisiones de ambos órganos sociales.
The presence of the notary public in the Board meetings and his certiication of corporate minutes. Regarding the amendment of article 170 of the General Corporations Law
Keywords: Board Of Directors; General Shareholders Meeting; Notary Public; Corporate Minutes; Notary Certiicate; Corporate Law; Notary Law; Directorio; Junta General de Accionistas; Notario; Actas Societarias; Actas Notariales; Derecho Societario; Derecho Notarial; https://purl.org/pe-repo/ocde/ford#5.05.00